As(III) removal from aqueous solution by katoite (Ca3Al2(OH)12). (December 2020) - Sha, Lin; Zou, Zhemin; Qu, Jun; Li, Xinfei; Huang, Yiyi; Wu, Chenjie; Xu, Zhigao
Abstract: As (III) is widely distributed in groundwater which is relatively harder to be removed comparing to As (V). Co-grinding Ca(OH)2 with Al(OH)3 was conducted to manufacture katoite (Ca3 Al2 (OH)12 ) for the complete removal of As(III) (concentration below drinking water standard of WHO (<10 ppb)) during one-step agitation operation. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TG), and X-ray photoelectron spectroscopy (XPS) were applied for the illustration of adsorption mechanism. Katoite could intercalate As(III) into the layered space forming arsenite pillared Ca-Al layered double hydroxide (LDH). The coexisting anions such as Cl −, SO4 2−, and NO3 − had minor effects on As (III) removal performance using katoite. Techno-economic analysis demonstrated the feasibility of large-scale katoite production and its practical application for As(III) polluted groundwater purification, especially in the undeveloped areas where groundwater was used as irrigation and drinking water. Graphical abstract: Image 1 Highlights: Co-milling Ca(OH)2 with Al(OH)3 to produce katoite ((Ca3 Al2 (OH)12 ). As(III) (concentration <50 ppm) removal by katoite forming arsenite pillared Ca-Al LDH. As(III) (concentration >50 ppm) precipitation by katoite forming calcium arsenite. Excellent adsorption selectivity of katoite toward As(III) over coexisting anions.